2010
DOI: 10.1097/ans.0b013e3181dbc60f
|View full text |Cite
|
Sign up to set email alerts
|

Somali Bantu Refugees in Southwest Idaho

Abstract: The Somali Bantu represent a subset of African refugees, many of whom are preliterate with no native written language. This population presents significant challenges for nurses and other healthcare providers. A community-based participatory research project using qualitative techniques to combine community and cultural assessment was conducted over 18 months. A thorough description of methodology and results are provided. The results of the assessment are discussed as well as implications for healthcare provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Traditionally, Somali Bantus rely on spiritual practices such as prayer, ceremony and herbal remedies to treat illness (Springer, Black, Deckys, & Soelberg, 2010). A qualitative inquiry conducted by Pavlish, Noor and Brandt (2010) supported that Western medicine did not align with Somali women's views of health care.…”
Section: Somali and Somali Bantu Perceptions Of Illness And Health mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, Somali Bantus rely on spiritual practices such as prayer, ceremony and herbal remedies to treat illness (Springer, Black, Deckys, & Soelberg, 2010). A qualitative inquiry conducted by Pavlish, Noor and Brandt (2010) supported that Western medicine did not align with Somali women's views of health care.…”
Section: Somali and Somali Bantu Perceptions Of Illness And Health mentioning
confidence: 99%
“…A qualitative inquiry conducted by Pavlish, Noor and Brandt (2010) supported that Western medicine did not align with Somali women's views of health care. Moreover, Somali Bantu refugee women are more likely to hold on to traditional healing methods than Somali Bantu men (Springer et al, 2010).…”
Section: Somali and Somali Bantu Perceptions Of Illness And Health mentioning
confidence: 99%
“…[4, 10, 21, 22]), all participants in this study reported problems with communication. Schweitzer et al [22] found that 70% of Burmese refugees reported limited language proficiency of the new country is a serious issue.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, refugees need to navigate through healthcare services in a new country [10, 21, 23]. Many participants also reported this as a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation